1988
DOI: 10.1007/bf01454315
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic, cadmium, lead and mercury in meat, livers and kidneys of sheep slaughtered in The Netherlands

Abstract: The results obtained between 1981 and 1986 in a Dutch monitoring programme investigating the presence of arsenic, cadmium, lead and mercury in meat, livers and kidneys of sheep are presented. For the meat, livers and kidneys, the median values were 0.001, 0.003, and 0.007 mg/kg (fresh weight) for arsenic; 0.003, 0.054, and 0.098 mg/kg for cadmium; 0.04, 0.85, and 0.36 mg/kg for lead; and 0.001, 0.002, and 0.007 mg/kg for mercury. During the reported period, no clear trends were observed. The results are compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 17 publications
2
7
0
Order By: Relevance
“…However, a study in Egypt indicated that relatively high mean value of Pb residues in muscles of sheep, and it was 1.884 ppm (FAO/WHO, 1992). The Pb content in the liver was relatively high but it fluctuated throughout the year and the highest concentration was estimated during summer (Vos et al, 1991). However, Pb concentration in the liver can reach up to 10 mg/kg in sheep reared in polluted areas.…”
Section: Results Inmentioning
confidence: 92%
See 2 more Smart Citations
“…However, a study in Egypt indicated that relatively high mean value of Pb residues in muscles of sheep, and it was 1.884 ppm (FAO/WHO, 1992). The Pb content in the liver was relatively high but it fluctuated throughout the year and the highest concentration was estimated during summer (Vos et al, 1991). However, Pb concentration in the liver can reach up to 10 mg/kg in sheep reared in polluted areas.…”
Section: Results Inmentioning
confidence: 92%
“…(2) The means of the Pb concentration in the mutton, liver and kidney of local and Australian sheep were very high and represent over 5 times in comparison to that recorded in other countries like Holland and Egypt (Boulis, 1993;Vos et al, 1991) and (Attala, 1998). (3) Although the mutton of the Australian sheep has a higher significant mean Pb concentration than the local and Chinese sheep, the means of Pb concentration in the mutton of local, Australian and Chinese sheep marketed in Jordan were very high when compared to that recorded in other countries over 3 times on average.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The method described by Vos et al (1991) and GonzalezWeller et al (2006) was adopted in the extraction of metals from edible parts. The ashed samples of liver and muscle tissues were mixed with 3 ml of 3 N nitric acid and dried on a hot plate at 120 ± 15°C for half an hour, then placed in muffle furnace and temperature raised to 450°C for 1 h; this step was repeated three times to get constant weight, from which one gram samples were removed from muffle furnace, cooled to room temperature (28 ± 5°C) and dissolved in 1 ml of 1 N hydrochloric acid.…”
Section: Digestion Of Edible Partsmentioning
confidence: 99%
“…Cadmium (Cd), lead (Pb), arsenic (As) and mercury (Hg) are nonessential biological metals that exhibit extreme toxicity, even at trace levels 11 . For instance, cadmium accumulation in the human body can induce skeletal damage, kidney dysfunction and reproductive deficiencies 12 , 13 ; Lead can significantly reduce semen quality, thus impairing human reproductive function 14 ; Arsenic can cause toxic and harmful biological effects such as liver, skin and bladder cancer 15 ; Mercury can cause adverse effects such as impair hearing, eyesight, and the nervous system 8 , 16 . The biological function of chromium is unclear, but when its concentration exceeds the threshold, it can cause damage to the liver, kidney, lungs and is recognized as a known carcinogen 9 , 17 .…”
Section: Introductionmentioning
confidence: 99%